Somatoform and Other Psychosomatic Disorders A Dialogue Between Contemporary Psychodynamic Psychotherapy and Cognitive Behavioral Therapy Perspectives (Springer International Publishing, 2018)
This intriguing volume presents the most contemporary views on the conceptualization and treatment of somatoform disorders and related conditions from experts in psychodynamic and cognitive behavioral approaches. It does so with respect to both perspectives, without advocating for either approach. By presenting expert views from diverse perspectives, the book raises, what is a central point in most of the chapters, that emotion, its processing and regulation, is a cornerstone of these disorders. The volume also highlights the role of pathogenic coping or defense mechanisms like dysfunctional avoidance (from a CBT perspective) and conversion (from the psychodynamic perspective) in the maintenance of psychosomatic symptoms. The volume's contents include detailed literature reviews on the most common-and most treatment-resistant-mind/body conditions, including chronic pain, responses to trauma, alexithymia, and the spectrum of health anxiety disorders. Noted experts distinguish between types of medically unexplained symptoms, discuss their complex processes, and provide models for intervention where cognitive-behavioral or psychodynamic approaches may be appropriate or effective. And a fascinating case study of a patient presenting multiple trauma-related disorders explores therapist resourcefulness over a course of shifting symptoms and frustrating setbacks. Among the topics covered: Maintaining mechanisms of health anxiety: current state of knowledge. Negative affect and medically unexplained symptoms. Alexithymia as a core trait in psychosomatic and other psychological disorders. Trauma and its consequences for body and mind. Embodied memories, a new pathway to the unconcious. Psychotherapy among HIV patients: a look at a psychoimmunological research study after 20 years. Health anxiety: a cognitive-behavioral framework. The wealth of options discussed in Somatoform and Psychosomatic Disorders offers health psychologists, psychiatrists, psychotherapists, counselors, and psychoanalysts bold new ideas for case formulation, treatment planning, and intervention with some of their most intractable cases.